Nonlinear mathematical physics and natural hazards : selected papers from the International School and Workshop held in Sofia, Bulgaria, 28 November-02 December, 2013 /: selected papers from the International School and Workshop held in Sofia, Bulgaria, 28 November-02 December, 2013. (2015) - Unknown
No abstract available